2015
DOI: 10.1093/jpids/piu145
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cultures for Persistent Fever in Neutropenic Pediatric Patients Are of Low Diagnostic Yield

Abstract: The incidence of bacteremia at the onset of pediatric febrile neutropenia (FN) at 2 academically linked institutions was 9.84%, and subsequent blood cultures performed for children with persistent FN yielded an incidence of 4.21%. Until the risk factors for new-onset bacteremia in patients being treated for FN can be identified and diagnostic methods can be improved, compliance with national guidelines is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 9 publications
4
21
0
Order By: Relevance
“…Studies evaluating the utility of subsequent blood cultures in the setting of an initially negative culture have found an initial prevalence of bacteremia of 9.8–18.4%, and a 0.9–10.9% prevalence of subsequent blood culture positivity . A study of adult and pediatric hematopoietic stem cell transplant (HSCT) patients found one new positive blood culture in 109 patients after day 1 (0.9%) in a retrospective review .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies evaluating the utility of subsequent blood cultures in the setting of an initially negative culture have found an initial prevalence of bacteremia of 9.8–18.4%, and a 0.9–10.9% prevalence of subsequent blood culture positivity . A study of adult and pediatric hematopoietic stem cell transplant (HSCT) patients found one new positive blood culture in 109 patients after day 1 (0.9%) in a retrospective review .…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective review of pediatric solid oncology patients found that in 220 FN episodes in 105 patients, 24 (10.9%) new positive cultures were found positive after day 1, but neither specific timing nor determination of pathogen versus contaminant was reported . Another retrospective chart review of pediatric solid tumor patients found two pathogens after day 1 in 193 FN episodes, without comment on change in clinical status . A study examining risk factors of subsequent blood culture positivity in HSCT pediatric patients found a 1.5% incidence of new blood stream infection (BSI) per day, with risk factors including previous BSI within 30 days and increased length of time between fevers .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While patients presenting with neutropenic fever have high rates of initial bacteraemia (Freifeld et al , ), follow‐up blood cultures appear to have a very low yield (Serody et al , ; Wattier et al , ; Neemann et al , ). As previous studies have examined only small numbers of patients, we used a data linkage approach to assess the frequency and predictors of new isolates in follow‐up blood cultures during episodes of suspected neutropenic sepsis.…”
Section: Results Of the Multivariate Analysis Using Generalised Estimmentioning
confidence: 99%